2016
DOI: 10.1016/j.jobcr.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of salivary malondialdehyde in assessment of oxidative stress among diabetics

Abstract: MDA was detectable in saliva in both diabetic and control groups. There was a positive significant correlation between salivary and serum MDA in diabetic and control subjects. Hence, salivary MDA appears to be an indicator of serum MDA concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…There was highly significant positive correlation between salivary and serum MDA levels (p=0.0007). Smriti et al 17 found strong and significant positive correlation between serum and salivary MDA in both controls and diabetics. This indicates that salivary MDA in diabetic patients may result from a state of systemic dyslipidemia and serum composition is reflected in the saliva composition.…”
Section: Discussionmentioning
confidence: 96%
“…There was highly significant positive correlation between salivary and serum MDA levels (p=0.0007). Smriti et al 17 found strong and significant positive correlation between serum and salivary MDA in both controls and diabetics. This indicates that salivary MDA in diabetic patients may result from a state of systemic dyslipidemia and serum composition is reflected in the saliva composition.…”
Section: Discussionmentioning
confidence: 96%
“…[31] It should be noted that the MDA content increases in case of lung cancer, but we found no statistically significant increase in this indicator even despite the numerous confirmations of this fact in the literature. [22][23][24][25][26][27][28][29][30] During the performed studies, we have elicited the fact of an increase in the level of MM, which is an indirect evidence of excessive generation of active oxygen metabolites: Superoxide radicals and hydrogen peroxide. [36] Hydroxyl radicals are capable to damage the phosphoglyceride membrane structures of cell membranes and its organelles.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Thereat, the saliva adequately reflects the biochemical status and physiological state of a person, which allows using it in clinical laboratory diagnostics. [19,20] There is a number of scientific works [21][22][23] dedicated to the study of indicators of endogenous intoxication and lipid peroxidation in saliva; however, the overwhelming majority of studies are limited to an evaluation of the MDA content. [22,24,25] The changes in the lipid peroxidation processes in the saliva of patients with oral cavity precancer and cancer are described by the example of MDA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of positive correlation between serum and salivary MDA concentration, this new method has the potential to become a new standard technique for the assessment of oxidative stress in clinical practice. Several studies described MDA determination from biological samples, but most of them have reduced sensi-tivity and specificity, they also have long analysis time [23,24]. The purpose of this work is to develop a fast and highly sensitive HPLC method with visible domain detection for measurement of malondialdehyde in human serum and saliva samples.…”
Section: +mentioning
confidence: 99%